Sustaining host plant resistance derived through conventional and biotechnological means - Maredia, K.M.
Sumario (En)
11 ref.
Keywords: BIOTECNOLOGIA; HIBRIDOS; RESISTENCIA A AGENTES DAÑINOS; VARIEDADES; TRANSGENICOS